POST PLACENTAL INTRAUTERINE CONTRACEPTIVE DEVICE INSERTION: A PROMISING CONTRACEPTIVE APPROACH - Tahira Khalid; Tehmina Yousaf; Sadia Irum; Uzma Javed (Pakistan Armed Forces Medical Journal, 2019)
Objective: To evaluate efficacy and safety of post placental intrauterine contraceptive device (PPIUCD) insertion during cesarean section.